Analisis Peran Badan Kesatuan Bangsa dan Politik dalam Merawat Kerukunan Masyarakat di Kabupaten Sintang, Kalimantan Barat - Yohanes, Yohanes; Rochmawati, Ida; Juliana, Ari (Jurnal Ilmiah Administrasi Publik, 2023)
Indonesia, which is diverse in social, cultural, economic and political settings at regional, national and global levels, requires the strength of harmony as social capital. The aim of this research is to explain the effectiveness of the role of the Kesbangpol Agency in maintaining community harmony in Sintang district. The research method used is qualitative, case study. Data collection techniques use interviews, observation and document study. The data analysis technique uses inductive interactive analysis. The research results show that there are three effective roles of the Kesbangpol agency. The role of efficiency is manifested in the vision, mission and program of community harmony in fostering ideology and national insight in the context of political dynamics in areas with various ideological challenges in border areas. The role of balance can be seen from the adaptation and collaboration of the Kesbangpol Agency with various agencies in maintaining harmony and preventing social, political and economic conflicts in the dynamics of SARA conflicts and economic and social problems during the Covid 19 pandemic in border areas. The anticipatory role is manifested in the ability to anticipate early on social, economic and political conflicts related to SARA, resulting in social control and the creation of early vigilance, preventing the spread of conflicts related to SARA that occurred in the last five years in Sintang district. In order for the Kesbangpol Agency's role to be more effective in maintaining harmony, it is necessary to strengthen its early detection capabilities as well as team and program collaboration to expand the realization of the harmony conscious village program throughout the Sintang district and continuously develop ideology and national insight for the community as well as strengthening the ideology of Pancasila and nationalism in border area.